2020
DOI: 10.1002/da.23071
|View full text |Cite
|
Sign up to set email alerts
|

COVID stress syndrome: Concept, structure, and correlates

Abstract: Background Research shows that the COVID Stress Scales have a robust multifactorial structure, representing five correlated facets of COVID‐19‐related distress: (a) Fear of the dangerousness of COVID‐19, which includes fear of coming into contact with fomites potentially contaminated with SARSCoV2, (b) worry about socioeconomic costs of COVID‐19 (e.g., worry about personal finances and disruption in the supply chain), (c) xenophobic fears that foreigners are spreading SARSCoV2, (d) traumatic stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
671
5
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(742 citation statements)
references
References 15 publications
47
671
5
19
Order By: Relevance
“…Among the worries, worry over one's own personal finances was clearly and consistently the one most linked to depression, anxiety, and insomnia. This finding relates to recent results by Taylor et al [44] demonstrating a strong association between fear of perceived threat of COVID-19 and COVID-19related socioeconomic consequences.…”
supporting
confidence: 90%
“…Among the worries, worry over one's own personal finances was clearly and consistently the one most linked to depression, anxiety, and insomnia. This finding relates to recent results by Taylor et al [44] demonstrating a strong association between fear of perceived threat of COVID-19 and COVID-19related socioeconomic consequences.…”
supporting
confidence: 90%
“…Domestic and foreign literature was reviewed to create an item pool, and the scales that may be relevant were examined. Two scales named The Fear of COVID-19 Scale (Ahorsu et al, 2020) and COVID Stress Scales (Taylor et al, 2020), which may be related to the subject, were found in the literature. No scale related to the "COVID-19 Psychological Destruction Scale" was found in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Health anxiety and illness attitudes were associated with virus anxiety, concerns about SARS-CoV-2, COVID-19 related stress, depressive symptoms, (generalized) anxiety, death anxiety and the likelihood of self-isolation [ 13 , 15 , 16 , 17 , 18 ]. While, the latter mentioned studies did not specifically differentiate between health anxiety emerged due to COVID-19 and health anxiety existing “before” COVID-19, Taylor et al [ 19 , 20 ] were the first to ask for “premorbid” health anxiety and found a significant correlation with COVID-19-related distress.…”
Section: Introductionmentioning
confidence: 99%